Effects of chronic alcohol use disorder and alcohol withdrawal on phosphate, magnesium, and calcium (Swiss Medical Weekly, 2025)
In addition to frequent hyponatraemia, excessive and chronic alcohol consumption can lead to disturbances in phosphorus, magnesium and calcium balance.Due to the close physiological interactions between phosphorus, magnesium and calcium, changes in one or more of these substances can lead to a life-threatening vicious cycle.Electrolyte imbalances are common during alcohol withdrawal and require careful monitoring and treatment.